A Discussion of Reinforcement Timing Optimization for Main Inclined Shaft Roadway with Water Seepage - Minglei Zhang; Chaoyu Chang; Wen Cao (Geofluids)
The infiltration and physical and chemical effects of fissure water often have a degrading effect on the strength and bearing capacity of the surrounding rock of the roadway. With the increase of the time of water infiltration, the roadway deformation increases exponentially, resulting in a higher risk of roadway destruction. In this paper, targeting at the supporting and protection issues associated with the main inclined shaft during the water-drenching, a numerical simulation method was established to evaluate the impact of the fissure water on the deformation of the surrounding rock of the roadway, and a solution to control the top water in main inclined shafts by grouting was proposed. Through the numerical simulation method, the effective penetration range of the slurry in the surrounding rock and the variation of the tunnel deformation with the grouting timing were studied. A method of combining numerical simulation with on-site monitoring to determine a reasonable grouting timing was proposed. The field application suggests that grouting at a reasonable timing can effectively control the influence of seepage water from the roof crack of the main inclined shaft on the deformation of the roadway surrounding rock, improve the integrity of the roadway surrounding rock, increase the bearing capacity of the support, and maintain the safety and stability of the roadway surrounding rock of the main inclined shaft. Furthermore, this study can provide insightful references to the grouting reinforcement adopted by similar main inclined shafts.